Imaging findings of fibrosis in pulmonary sarcoidosis - Sawahata, Michiru; Yamaguchi, Tetsuo (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: In pulmonary sarcoidosis, respiratory tract lesions almost always appear, and residual lung shadows require treatment in about 20% of cases. Pulmonary fibrosis is among the three leading causes of death. Treatment strategies are urgently needed to inhibit the progression of pulmonary fibrosis by combining antifibrotic drugs and immunosuppressive drugs such as corticosteroids. Establishing consensus on the process of pulmonary fibrosis progression is important for determining the most effective treatment. Our review: Among more than 2500 cases of sarcoidosis treated at our hospital, cases that led to chronic respiratory failure were analyzed for CT findings of pulmonary fibrosis. Early in sarcoidosis, granulomatous lesions appeared along the bronchovascular bundle. As pulmonary fibrosis progressed, a central consolidation developed on the central side in the direction of lymph flow, a peripheral consolidation developed on the pleural side, and a central-peripheral band developed connecting the two. Infiltrative or wedge-shaped shadows sometimes formed in the immediate subpleural area, appearing as a pleuroparenchymal fibroelastosis-like lesion. Traction bronchiectasis may form cysts at the periphery or may congregate to form a honeycomb lung-like structure. Combination of these lesions led to shrinkage of the upper lobe. Patients with multiple peripheral cysts/bullae had a unique disease course characterized by wheezing and concomitant pulmonary hypertension and pulmonary aspergillosis. Conclusion: Further understanding of the process of pulmonary fibrosis progression is needed. Summarizing imaging findings and understanding their contribution to respiratory impairment will contribute to comprehensively evaluating the stages of pulmonary fibrosis progression and establishing an optimal treatment strategy.